2014
DOI: 10.1530/joe-14-0398
|View full text |Cite
|
Sign up to set email alerts
|

Liver immune responses to inflammatory stimuli in a diet-induced obesity model of zebrafish

Abstract: Obesity-and metabolic syndrome-related diseases are becoming important medical challenges for the western world. Non-alcoholic fatty liver disease (NAFLD) is a manifestation of these altered conditions in the liver, and inflammation appears to be a factor that is tightly connected to its evolution. In this study, we used a diet-induced obesity approach in zebrafish (Danio rerio) based on overfeeding to analyze liver transcriptomic modulation in the disease and to determine how obesity affects the immune respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 57 publications
4
26
2
2
Order By: Relevance
“…Weight gain; increased BMI; triglycerides accumulation; adipocyte hyperplasia; ectopic adipose tissue; increased expression of adiponectin, adiponectin receptors, leptin receptor; increased inflammatory molecules TNFα, IL1β, MMP2 and MMP9 [104] DIO models Artemia overfeeding Adult Overfeeding with nauplii artemia for 8 wk Increased BMI; high plasma triglycerides; hepatosteatosis [106] Chow overfeeding Adult Overfeeding with standard fish chow for 8 mo Weight gain; hepatosteatosis [109] Zebrafish obesogenic test (OZ) Larva High-fat diet based in hardboiled chicken egg-yolk ad libitum during one day…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Weight gain; increased BMI; triglycerides accumulation; adipocyte hyperplasia; ectopic adipose tissue; increased expression of adiponectin, adiponectin receptors, leptin receptor; increased inflammatory molecules TNFα, IL1β, MMP2 and MMP9 [104] DIO models Artemia overfeeding Adult Overfeeding with nauplii artemia for 8 wk Increased BMI; high plasma triglycerides; hepatosteatosis [106] Chow overfeeding Adult Overfeeding with standard fish chow for 8 mo Weight gain; hepatosteatosis [109] Zebrafish obesogenic test (OZ) Larva High-fat diet based in hardboiled chicken egg-yolk ad libitum during one day…”
Section: Resultsmentioning
confidence: 99%
“…adult zebrafish was generated by feeding them two times the standard fish chow than the controls [109] . DIO animals showed increased total weight, showed liver steatosis, as well as the overexpression of tac4, col4a3, col4a5, lysyl oxidases and genes involved in retinoid metabolism.…”
Section: Diet Induced Obesity Modelsmentioning
confidence: 99%
“…[17] Another animal model, such as zebra fish have been observed as an obesity model and this model is very appropriate to be developed as an obesity model through high-fat diet administration. [8][9][10][11][12][13][14][15][16][17][18] In the recent study, we use zebra fish (D. rerio) to explore the association between high-fat diet consumption, obesity, and metabolic syndrome. The results of this study found that high-fat-diet-induced obesity in zebrafish has an impact on elevated metabolic syndrome and the development of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Zebrafish, like humans, will overeat if exposed to large amounts of food [98]. Although studies have examined the effects of overfeeding in zebrafish [99][100][101], few studies have utilized these animals as a model to study obesity, and to a lesser extent to study the effects of brain aging.…”
Section: Overfeedingmentioning
confidence: 99%